INVENTORY OF REGIONAL POTENTIAL FOR LEADING COMMODITIES IN SUPPORTING REGIONAL ECONOMIC COMPETITIVENESS IN LAREH SAGO HALABAN DISTRICT, LIMAPULUH KOTA REGENCY - Elviati; Dara Latifa; Fastabiqul Khairad; Novfirman; Farid Azel; Ispinimiartriani; M. Syakib Sidqi (RADJA PUBLIKA, 2023)
Commodity development in rural areas is a major concern to support regional economic competitiveness. This regional development aims to build and increase interdependence and interaction between economic systems, humans or communities in the environment and natural resources. Each region has its own advantages in developing commodities which are considered capable of improving the regional economy which is supported by the competitiveness of the commodities in that region. Lareh Sago Halaban district has superior commodities such as rubber, coconut, palm sugar, areca nut and gambier which can be developed for the community to increase economic competitiveness.